A preliminary assessment of uncertainties attributed by analysts, array types and processing algorithms for microtremor observations, via the COSMOS Blind Trials. Issue 1 (1st December 2019) - Asten, Michael W.; Yong, Alan; Foti, Sebastiano; Hayashi, Koichi; Martin, Antony; Stephenson, William J.; Cassidy, John F.; Coleman, Jacie
Summary: The blind trial studies conducted for the 2006 3rd International Symposium on the Effects of Surface Geology (Grenoble, France) and the 2015 Inter-comparison of Methods for Site Pa rameter and Veloci ty Profile Charac terization (InterPACIFIC) Workshop (Turin, Italy) evaluated the utility of microtremor array methods for characterizing seismic site conditions. These studies used a multiplicity of arrays but left an open question as to whether (and under what) conditions might sparse (low-cost) arrays be technically sufficient for the task. Similar questions arise when designing arrays for use in mapping cover thickness or buried high-velocity layers in mineral exploration. In this study, the Consortium of Organizations for Strong Motion Observation Systems (COSMOS) blind trials used microtremor array data from four sites with geology ranging from deep alluvial valleys to an alpine valley. Data were incrementally released to approximately a dozen analysts in four phases: (1) 2-station linear arrays; (2) sparse triangular arrays; (3) complex nested triangular or circular arrays; (4) all available geological control including drillhole data. While data from one site consisted of recordings from 3-component sensors, the other three sites consisted of data from vertical-component sensors only. The sites covered a range of noise source distributions, ranging from one site with a highly directional microtremor wave field, to others with distributed or omni-directional wave fields. Here, we review the results based on the different processing algorithms (e.g. beam-forming, spatial autocorrelation, seismic interferometry) as applied by the analysts to the incrementally released data, and then compare the effectiveness between the differing wave-field distributions. The results of the study will aid in building an evidence-based consensus on preferred cost-effective arrays and processing methodology for future studies of earthquake hazard site-effects and cover thickness studies in mineral exploration.